2009
DOI: 10.1182/blood-2008-04-150987
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ligation-dependent CD45RB enzymatic activity negatively regulates lipid raft signal transduction

Abstract: CD45 is the most prominent membrane protein on lymphocytes. The function and regulation of this protein tyrosine phosphatase remain largely obscure, mainly because of the lack of a known ligand, and it still remains unknown whether such tyrosine phosphatases are subject to extracellular control at all. We report that an anti-CD45RB antibody (Ab) that prevents rejection and induces tolerance activates CD45RB tyrosine phosphatase enzymatic activity in T lymphocytes, allowing us to directly monitor the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…We determined that the anti-rat CD45RC OX22 induced tolerance and showed high killing activity in vitro. This is reminiscent to anti-CD45RB mAb effects, since comparison of two different anti-CD45RB mAb showed that the one effective for prolonging allograft survival was also more effective in killing cells through apoptosis (43,(56)(57)(58). A chimeric mAb binding to both CD45RB and CD45RO has been described to prevent islet allograft rejection in mice through depletion of memory T cells (57 This, together with the increased suppressive activity of Tregs when adoptively transferred or used in vitro, indicates that their function is likely increased through activation on alloantigens.…”
Section: Discussionmentioning
confidence: 99%
“…We determined that the anti-rat CD45RC OX22 induced tolerance and showed high killing activity in vitro. This is reminiscent to anti-CD45RB mAb effects, since comparison of two different anti-CD45RB mAb showed that the one effective for prolonging allograft survival was also more effective in killing cells through apoptosis (43,(56)(57)(58). A chimeric mAb binding to both CD45RB and CD45RO has been described to prevent islet allograft rejection in mice through depletion of memory T cells (57 This, together with the increased suppressive activity of Tregs when adoptively transferred or used in vitro, indicates that their function is likely increased through activation on alloantigens.…”
Section: Discussionmentioning
confidence: 99%
“…A kinase peptide substrate array consisting of 1,024 peptides with specific phosphorylation sites was used to comprehensively evaluate the kinome during osteoblastic differentiation, as previously described [Diks et al, 2004;Lö wenberg et al, 2005;Tuynman et al, 2008;Parikh et al, 2009]. After treatment with AA/b-GP for 7 days, the cells were washed in ice-cold phosphatebuffered saline (PBS) and harvested in lysis buffer (Pierce Biotechnology, Inc.) supplemented with protease and phosphatase inhibitors (Roche).…”
Section: Kinome Array Analysismentioning
confidence: 99%
“…Data were exported to a spreadsheet for further analysis. The raw data were normalized to the 90th percentile, as described previously (15)(16)(17)(18). From this data, the heat map in Figure 1 was constructed in R 2.12.0 (R Foundation for Statistical Computing, Vienna, Austria) using the heatmap.2 function of the gplots library, making use of the hclust function set using complete-linkage.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2B depicts signaling events centered by SRC (spots 52, 590 and 736). The SRC kinases protooncogene tyrosineprotein kinase Fyn (FYN) (spots 196 and 318) and leukocyte-specific protein tyrosine kinase (LCK) (spots 59 and 457) display enhanced activity after 24 and 48 h respectively (17,31,32). SRC-inhibiting kinase c-src tyrosine kinase (CSK) (spot 836) (33) activity was diminished after 6 and 24 h, intermediate between CSK and SRC, v-yes-1 Yamaguchi sarcoma viral-related oncogene homolog (LYN) (spot 11) (34) activity was enhanced after 48 h. These signals toward SRC balance out and result in overall activation of SRC kinase.…”
Section: K Pneumoniae Pneumonia Kinome Profilementioning
confidence: 99%